KETERKAITAN SELF EFFICACY DAN SELF ESTEEM TERHADAP PRESTASI BELAJAR MAHASISWA - Adiputra, Sofwan (JURNAL FOKUS KONSELING, 2015)
AbstractÂ This study aims to measure the relationship between self-efficacy and self-esteem on student achievement. The research was conducted using quantitative descriptive analysis by the method of field research, which is conducted by survey to respondents. To analyze the data using correlational analysis techniques and multiple regression analysis techniques. The conclusion from this study showed that the relationship of self-efficacy and self-esteem on learning achievement.Â Keywords: Self Efficacy, Self Esteem, Achievement